SANDSTONE RESERVOIR 1600 DURI FORMATION CHARACTERIZATION TO OPTIMIZE BANGKO FIELD PRODUCTION - Raharjo, Cahyo
Bangko field is a faulted anticline hydrocarbon trap and located in Rokan Block. Peripheral injection method implementation in this field give positive result on increasing oil production. This method was effective on good porosity and permeability reservoir, that can increase the recovery factor. But Peripheral injection method was not effective on low porosity and permeability reservoir, that can not optimize the resource using vertical well. The failure of this method is due to reservoir D1600 heterogenity in Bangko field. Another technology that has been tried to increase recovery factor in this reservoir is horizontal well drilling which targeting low permeability reservoir. But most of them is not effective also. Unsucsessfull of this method is suspected due to improper horizontal well trajectory. This research was conducted to see facies, its distribution and geometry that construct D1600 Duri Formation sandstone reservoir, because it is suspected lateral and vertical reservoir quality variation will influence horizontal well result. Main data that used for analysis are log, core and 3D seismic data. First step is sedimentation analysis that consist of core description, facies identification based on Gamma Ray log pattern. Second step is sequen stratigrafi interpretation and well correlation. Third step is integration with 3D seismic data to obtain profile of facies geometry and reservoir quality distribution. Based on sedimentology analysis on core dana GR curve data can be conclude that D1600 Duri Formation sandstone reservoir consist of bioturbated sandstone facies and deposited in tidal deltaic environment. Based on sequence stratigraphy analysis, D1600 Duri Formation reservoir can be devided into two parasequen, Parasequence A which is fluvial dominated deltaic deposit and Parasequen B which is marine dominated deltaic deposit. Each parasequen consist of sand ridge and channel. On Parasequen A thickness mapping, thickness of channel is controlled by existing incised valley morphology. Parasequen B was deposited after Parasequen A filled incised valley morphology, that its distribution was not controlled by those morphology. Seismic analysis shows seismic similarity trending NE-SW that indicates sedimentation direction 45 degree. Formation Evaluation analysis shows Parasequen A has higher permeability than parasequen B. Low permeability zone of Parasequen B is located in the upper part with higher GR curve value. On low permeability zone mapping, we found two main zone of 10 feet thickness. Validation result shows low permeability zone at the northen part of Bangko field has been exploited using existing horizontal well.